2021
DOI: 10.1186/s42238-021-00078-w
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol use and effectiveness: real-world evidence from a Canadian medical cannabis clinic

Abstract: Background Cannabidiol (CBD) is a primary component in the cannabis plant; however, in recent years, interest in CBD treatments has outpaced scientific research and regulatory advancement resulting in a confusing landscape of misinformation and unsubstantiated health claims. Within the limited results from randomized controlled trials, and lack of trust in product quality and known clinical guidelines and dosages, real-world evidence (RWE) from countries with robust regulatory frameworks may fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 48 publications
1
31
0
2
Order By: Relevance
“…The study highlighted perceived benefits in conditions where medical cannabis had not yet been licensed Gulbransen et al [ 39 ] An audit of all patients who presented to a Cannabis Care clinic in New Zealand. This study highlighted the anxiolytic effects of cannabidiol Rapin et al [ 40 ] A retrospective observational study looking at patients who had been prescribed CBD treatment from data collated from a network of clinics Analysis of registries Habib et al [ 27 ] Looked at the efficacy of medical cannabis for treatment of fibromyalgia. It used data from two hospital registries.…”
Section: Types Of Real-world Evidence For Medical Cannabismentioning
confidence: 99%
“…The study highlighted perceived benefits in conditions where medical cannabis had not yet been licensed Gulbransen et al [ 39 ] An audit of all patients who presented to a Cannabis Care clinic in New Zealand. This study highlighted the anxiolytic effects of cannabidiol Rapin et al [ 40 ] A retrospective observational study looking at patients who had been prescribed CBD treatment from data collated from a network of clinics Analysis of registries Habib et al [ 27 ] Looked at the efficacy of medical cannabis for treatment of fibromyalgia. It used data from two hospital registries.…”
Section: Types Of Real-world Evidence For Medical Cannabismentioning
confidence: 99%
“…For instance, in our cohort for anxiety, 54% of 3,350 responses at baseline were normal (<8), mild/moderate 14%, severe 16%, extremely severe 16%. Similarly other observational studies have shown effect on moderate to severe symptoms of anxiety, but not mild symptoms of anxiety [39]. Further sub analysis of the AECeR registry will be conducted to determine outcome differences in different severity categories.…”
Section: Discussionmentioning
confidence: 91%
“…The ISI uses a 5-point Likert scale of 0-4 to rate each item (0 = no problem; 4 = very severe problem), yielding a total score ranging from 0 to 28. The total score is interpreted as follows: absence of insomnia (0-7); sub-threshold insomnia (8)(9)(10)(11)(12)(13)(14); moderate insomnia (15)(16)(17)(18)(19)(20)(21); and severe insomnia (22)(23)(24)(25)(26)(27)(28).…”
Section: Description Of the Validated Questionnaires Presentedmentioning
confidence: 99%
See 1 more Smart Citation
“…There are also a significant number of claims in the media that are difficult to validate but influence patients' consumption of cannabinoid products [17,19,25,[35][36][37][38]. Patients often consume cannabinoids regardless of their efficacy [39,40]. Other confounding variables affecting the assessment of cannabinoid properties are the lack of compound standardization and the increasing variability in their strength and composition [17,19,35,36].…”
Section: Introductionmentioning
confidence: 99%